Anthropogenically induced changes in sediment and biogenic silica fluxes in Chesapeake Bay - Colman, S. M.; Bratton, J. F. (Geology, 2003)
Sediment cores as long as 20 m, dated by C-14, Pb-210, and Cs-137 methods and pollen stratigraphy, provide a history of diatom productivity and sediment-accumulation rates in Chesapeake Bay. We calculated the flux of biogenic silica and total sediment for the past 1500 yr for two high-sedimentation-rate sites in the mesohaline section of the bay. The data show that biogenic silica flux to sediments, an index of diatom productivity in the bay, as well as its variability, were relatively low before European settlement of the Chesapeake Bay watershed. In the succeeding 300400 yr, the flux of biogenic silica has increased by a factor of 4 to 5. Biogenic silica fluxes still appear to be increasing, despite recent nutrient-reduction efforts. The increase in diatom-produced biogenic silica has been partly masked (in concentration terms) by a similar increase in total sediment flux. This history suggests the magnitude of anthropogenic disturbance of the estuary and indicates that significant changes had occurred long before the twentieth century.
632uhTimes Cited:47Cited References Count:35